2017
DOI: 10.1016/j.syapm.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia strains in cryptic species of the Anastrepha fraterculus complex (Diptera, Tephritidae) along the Neotropical Region

Abstract: Infection by Wolbachia was described previously in eleven species of Anastrepha fruit flies some of which are important pests of fruticulture. One such species is the nominal Anastrepha fraterculus, the South American fruit fly, which actually comprises a complex of cryptic species. The suggestions of using Wolbachia for the control of these pest species, make imperative a more precise characterization of the existing strains of the bacteria. In this study, population samples of the A. fraterculus complex from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
(116 reference statements)
1
13
1
2
Order By: Relevance
“…These patterns suggest the existence of one or several Wolbachia strains harboured by different A. obliqua populations. Similar post‐zygotic isolation patterns have been found between cryptic species in the A. fraterculus complex (Devescovi et al., ), which harbour different strains of Wolbachia (Prezotto, Perondini, Hernández‐Ortiz, Marino, & Selivon, ; Selivon et al., , ). Exploring the existence of the bacteria and characterizing its different strains among A. obliqua populations are important since it could facilitate colonization, strain refreshment, efficient mass rearing for application of the SIT, and eventually lead to the development of the incompatible insect technique (IIT) (Zhang, Lees, Xi, Bourtzis, & Gilles, ).…”
Section: Discussionsupporting
confidence: 63%
“…These patterns suggest the existence of one or several Wolbachia strains harboured by different A. obliqua populations. Similar post‐zygotic isolation patterns have been found between cryptic species in the A. fraterculus complex (Devescovi et al., ), which harbour different strains of Wolbachia (Prezotto, Perondini, Hernández‐Ortiz, Marino, & Selivon, ; Selivon et al., , ). Exploring the existence of the bacteria and characterizing its different strains among A. obliqua populations are important since it could facilitate colonization, strain refreshment, efficient mass rearing for application of the SIT, and eventually lead to the development of the incompatible insect technique (IIT) (Zhang, Lees, Xi, Bourtzis, & Gilles, ).…”
Section: Discussionsupporting
confidence: 63%
“…The presence of the same wsp gene sequence in different populations of A. fraterculus does not necessarily mean that they are infected with identical Wolbachia strains [16,119]. The Wolbachia infection status of several morphotypes of the A. fraterculus cryptic species complex (including A. fraterculus sp.1) was recently published by Prezotto et al [93]. The information provided by these authors with respect to Wolbachia sequence variants infecting different A. fraterculus populations from Argentina (either using MLST or wsp HVR analyses) differs from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The information provided by these authors with respect to Wolbachia sequence variants infecting different A. fraterculus populations from Argentina (either using MLST or wsp HVR analyses) differs from our findings. More knowledge regarding the origin of the samples and the number of individuals analyzed by Prezotto et al [93] are needed in order to compare the results obtained in the two studies. Moreover, the same authors suggested a potential association between specific Wolbachia strains and distinct A. fraterculus morphotypes, which could act as a reinforcing factor in the diversification processes, providing also, some evidence of the possible way of transmission of Our crossing experiments showed a detrimental effect during the development for crosses involving Af-Cast-1 females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based mostly on PCR and sequencing approaches, ˜66% of ˜86 tephritid species screened have at least one record of positive Wolbachia infection (excluding pseudogenes) in laboratory and natural populations (Table S1; only supergroups A and B have been found in tephritids). For the genus Anastrepha , all but one species ( A. ludens ) of 17 screened to date harbor Wolbachia [142, 144148, 149; and this study, 150]. Most Anastrepha species harbor Wolbachia strains assigned to supergroup A. Anastrepha striata Schiner and Anastrepha serpentina Wiedemann, however, harbor supergroup B in southern Mexico [147; and this study] and supergroup A in Brazil [146].…”
Section: Wolbachia In Tephritidsmentioning
confidence: 93%